Immobilization of Candida Rugosa lipase onto N-Vinyl-2-Pyyrolidone-Co-Styrene Hydrogel for use in enantioselective esterification - Harun, Aiza (1999)
Lipase from Candida rugosa was immobilized onto N-vinyl-2- pyyrolidone-co-styrene hydrogel (VP-co-ST) The crosslinker and the initiator used were EDMA and AIBN respectively Three different compositions of monomer were used, namely, (VP.ST)% , 1090, 5050 and 70 30 The VP-co ST hydrogel immobilized lipases were used in the enantioselective esterification of (R,S)-2-(4-chlorophenoxy) propanoic acid with n-tetradecanol The optimum reaction time was 24h for native and all immobilized lipases StudIes on the effect of percentages composition of monomers of the VP-co-ST hydrogel immobilized lipases showed that lipase immobilized onto hydrogel (VP ST)%, 1090 exhibited the highest percentages of enantiomeric excess at approximately 24% Generally, increasing the temperature of the enantioselective esterification increases the percentage of ester conversion for all VP-co-ST hydrogel immobilized lipases However, the percentages of enantiomeric excess increases up to 40°C and subsequently decreases At 40°C, the highest percentage of enantiomeric excess was shown by VP-co-ST hydrogel with compositlOn of monomer (VP ST)%, 1090 at 45% In the solvent effect studies, the percentage of ester conversion was higher in relative more polar organic solvents with log P value ranging from 20 to 30 for all immobilized lipases and native lipase The organic solvents such as toluene, chloroform and carbon tetrachloride showed higher percentage of ester conversion as compared with other solvents Immobilized lipases exhibited higher percentage of enantiomeric excess compared to the native lipase Higher percentage of enantiomeric excess were obtained when using chloroform and carbon tetrachloride at approximately 50% and 46% for VP-co-ST (VP ST)%, 5050 and (VP ST)%, 1090 respectively In the water activity studies, at optimum a, all immobilized lipases showed higher percentage of ester conversion compared to the native lipase at approximately 23%, 16% and 22% for VP-co-ST hydrogel with composition of monomer (VP ST)%, 1090, 5050 and 7030 respectively At optimum all, VPco- ST hydrogel immobilized lipase with composition of monomer (VP ST)%, 1090, 5050 and 7030 exhibited higher percentage of enantiomeric excess at approximately 40%, 21% and 28% respectively compared to the native lipase.